Scrambled or sunny-side up? : living your best life after losing your greatest love - Ridinger, Loren (Post Hill Press, 2025)
Scrambled or Sunny-Side Up? Living Your Best Life After Losing Your Greatest Love shares Loren Ridinger's life story--one that began with her husband JR Ridinger's bold vision to change the world through the power of the Internet. Alongside JR, she helped pioneer Market America, empowering thousands of entrepreneurs to succeed on their own terms using the power of online shopping. However, Loren's journey took a heartbreaking turn with JR's sudden passing after thirty-six years of partnership and marriage, leaving her to navigate overwhelming grief while trying to maintain the legacy they built together. In this book, Loren reveals how she found the strength to move through grief and start living fully by embracing each day--no matter what life served up next. This is more than just a memoir; it is a guide to turning loss into a powerful force for growth, and a reminder that within the dash lies the potential to create a life of meaning and impact.